2018
DOI: 10.1038/s41467-018-04125-8
|View full text |Cite
|
Sign up to set email alerts
|

Plasma cell differentiation is controlled by multiple cell division-coupled epigenetic programs

Abstract: The genomic loci associated with B cell differentiation that are subject to transcriptional and epigenetic regulation in vivo are not well defined, leaving a gap in our understanding of the development of humoral immune responses. Here, using an in vivo T cell independent B cell differentiation model, we define a cellular division-dependent cis-regulatory element road map using ATAC-seq. Chromatin accessibility changes correlate with gene expression and reveal the reprogramming of transcriptional networks and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
127
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 107 publications
(136 citation statements)
references
References 64 publications
8
127
1
Order By: Relevance
“…B cell differentiation into ASCs is known to be epigenetically regulated in a division dependent manner 56, 57 and cell cycle arrest facilitates terminal immune cell differentiation. 58 Top up-regulated TFs in the PR analysis of the day 7 antigen-specific T-bet hi over T-bet lo Bmem network, include SOX5 and E2F7 (Figure 2L), and these TFs inhibit cell proliferation and/or effect cell cycle arrest.…”
Section: Resultsmentioning
confidence: 99%
“…B cell differentiation into ASCs is known to be epigenetically regulated in a division dependent manner 56, 57 and cell cycle arrest facilitates terminal immune cell differentiation. 58 Top up-regulated TFs in the PR analysis of the day 7 antigen-specific T-bet hi over T-bet lo Bmem network, include SOX5 and E2F7 (Figure 2L), and these TFs inhibit cell proliferation and/or effect cell cycle arrest.…”
Section: Resultsmentioning
confidence: 99%
“…The transcriptional repressor EZH2 is required for maximal antibody secretion [31] and is overexpressed in SLE leukocytes [32]. While we show reduced antibody secretion in presence of the EZH2 inhibitor UNC1999 (Figure 3b), we see very little effects on proliferation (Figure 4) in contrast to other studies [33,34]. Of note is that the negative control compound for UNC1999, UNC2400, had similar effects as UNC1999 ( Figure 6) implicating off-target effects of UNC1999.…”
Section: Discussionmentioning
confidence: 50%
“…under preparation). In line with that hypothesis, recent studies on human and mouse B cells revealed that PC differentiation is coupled to division-dependent DNA demethylation and PC gene regulation [30][31][32] . Together with the results presented here, these observations suggest that the enhanced Cxcl12/Cxcr4 signaling mediated by the gain of function of the receptor together with the enhanced availability of its ligand, may contribute to a deep imprinting of the B cells that could partly explain the phenotypes observed.…”
Section: Discussionmentioning
confidence: 64%